The First Children’s Opera in Kutaisi by Kote Marjanishvili - Megrelidze, Gubaz (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2023)
This event is little known in the history of Georgian theater and even in Kutaisi. For the first time, this paper examines the children’s opera staged in Kutaisi by the great Georgian director, Kote Marjanishvili, marking the first children›s opera in Georgia. The report is based on the memories of the participants of the performance (K. Bokeria, L. Gegechkori, K. Sirbiladze, Farkosadze, Ak. Shanidze, N. Shvangiradze). This staging had a significant impact on the further development of children›s musical education. The public became interested in the development of musical education for the next generation. Rehearsals were held at a high professional level, which contributed to the development of the young actors’ abilities. Most importantly, this play is not mentioned in any book or collection published about Marjanishvili or the artist Petre Otkheli. This work will contribute to the comprehensive study of their creative heritage. At the beginning of 1930, the pioneering organization of the Kutaisi Music Technical College (currently the M. Balanchivadze Kutaisi School of Music), headed by Ak. Shanidze, asked Kote Marjanishvili to stage the children›s opera by composer Shalva Taktakishvili, „First May“ (the title was changed during the work to „Battle“ with a libretto by L. Gegechkori). Everything started when K. Marjanishvili attended a concert. After the concert, he came up with the idea of a larger-scale event and decided to stage a children’s opera. The age of the students did not exceed 10-12 years. About 200 children from different schools came to the selection process, which was led by K. Marjanishvili. Later, he attended 4-5 rehearsals, including the general rehearsal, but the premiere was held without him due to his departure to Moscow. The performance was prepared at the Kutaisi Drama Theater, where decorations, costumes, and props were made. During the process, the technical staff of the theater helped the students with great attention. Rehearsals were conducted by director Vakhtang Abashidze. The premiere took place on March 11, 1930, with great success.